Curcumin Administration on Proliferation and Apoptosis Index in Complete Hydatidiform Mole CellCulture - Tatit Nurseta; Yahya Irwanto; Imelda Imelda (Indonesian Socety of Obstetrics and Gynecology, 2016)
Objective: To investigate that curcumin can decreasing proliferation index and increasing apoptosis index. Method: This is an experimental non-blinded study with post test control group design, at Cell/Tissue Culture Laboratory at Medical Faculty of Brawijaya University. This study using CHM trophoblastic cell culture from CHM curettage patient, exposed by several doses of curcumin, 0, 50, 100, 200, 400 and 800 Î¼M, then examined by the method of MTT proliferation index and apoptosis index by the method of labeling DNA fragmentation TUNEL system. Data analyzed by one-way ANOVA. Result: In this study, the mean values obtained decrease in proliferation index with increasing doses of curcumin. Giving a dose of 200 Î¼M curcumin, 400 Î¼M and 800 Î¼M proved highly significant (p = 0.001) reduced proliferation index compared with the control and curcumin dose of 50 Î¼M and 100 Î¼M. From this research shows that there are significant differences in the increase of apoptosis index (p = 0.001) between the control group with curcumin dose group 200 Î¼M, 400 Î¼M and 800 Î¼M. But there was no significant difference in the mean of apoptosis index among the three dose groups. Conclusion: Giving curcumin dose of 200 Î¼M can decreasing the proliferation index and increasing the apoptosis index increases in CHM trophoblastic cell culture. [Indones J Obstet Gynecol 2016; 1: 37-41] Keywords: apoptosis index, curcumin, proliferation index